De Novo Design of Cell‐Penetrating Foldamers - Yokoo, Hidetomo; Misawa, Takashi; Demizu, Yosuke (Chemical record, 2020)
Cell‐penetrating peptides (CPPs) have gained much attention as carriers of hydrophilic molecules, such as drugs, peptides, and nucleic acids, into cells. CPPs are mainly composed of cationic amino acid residues, which play an important role in their intracellular uptake via interactions with acidic groups on cell surfaces. In addition, the secondary structures of CPPs also affect their cell‐membrane permeability. Based on this knowledge, a variety of cell‐penetrating foldamers (oligomers that form organized secondary structures) have been developed to date. In this account, we describe recent attempts to develop cell‐penetrating foldamers containing various building blocks, and their application as DDS carriers.